The Escherichia coli dnaN159 Mutant Displays Altered DNA Polymerase Usage and Chronic SOS Induction - Sutton, Mark D. (American Society for Microbiology, 2004)
The Escherichia coli β sliding clamp, which is encoded by the dnaN gene, is reported to interact with a variety of proteins involved in different aspects of DNA metabolism. Recent findings indicate that many of these partner proteins interact with a common surface on the β clamp, suggesting that competition between these partners for binding to the clamp might help to coordinate both the nature and order of the events that take place at a replication fork. The purpose of the experiments discussed in this report was to test a prediction of this model, namely, that a mutant β clamp protein impaired for interactions with the replicative DNA polymerase (polymerase III [Pol III]) would likewise have impaired interactions with other partner proteins and hence would display pleiotropic phenotypes. Results discussed herein indicate that the dnaN159-encoded mutant β clamp protein (β159) is impaired for interactions with the α catalytic subunit of Pol III. Moreover, the dnaN159 mutant strain displayed multiple replication and repair phenotypes, including sensitivity to UV light, an absolute dependence on the polymerase activity of Pol I for viability, enhanced Pol V-dependent mutagenesis, and altered induction of the global SOS response. Furthermore, epistasis analyses indicated that the UV sensitivity of the dnaN159 mutant was suppressed by (not epistatic with) inactivation of Pol IV (dinB gene product). Taken together, these findings suggest that in the dnaN159 mutant, DNA polymerase usage, and hence DNA replication, repair, and translesion synthesis, are altered. These findings are discussed in terms of a model to describe how the β clamp might help to coordinate protein traffic at the replication fork.